KONSEP JIHAD DALAM PERSPEKTIF ISLAM - Rif’at Husnul Ma’afi; Muttaqin Muttaqin (Universitas Darussalam Gontor, 2013)
It was a fatal mistake when terrorism equated with the doctrine of jihad in Islam. Terrorism in Arabic word termed as al-Irhab is not taught in the Qur’an. Even in Surah al-Anfal: 60 wrote the word “turhibûna”, but it can’t be used as the argument that terrorism is taught Islam. The word “turhibûna” here is more to frighten the enemy on the battlefield. By studying the turats and contemporary books, this simple paper triesto explore some of the misunderstandings about jihad. Then, those errors will be corrected by refering to the original opinion of the Muslim scholars, which in this paper refered to Ibn Qayyim al-Jawzi’s opinions. The results of the study showed that this misunderstanding lied on the meaning and concept of jihad. As understood by some people that jihad is a war in the path of Allah (fi sabilillah) only. In fact, the realm of jihadis very wide. Ibn Qayyim explained that jihad consists of 13 levels. These levels can be reduced to four parts, which one of them is fighting the infidels. Jihad against the infidels is not using the weapons. There are several steps that must be passed, so that jihad to infidels can be done. Of this division is also seen that the jihad war is not the onlysolution used by Islam in upholding Allah’s name (kalimatullah). So, this paper is expected to be able to describe the jihad in Islam based on the Qur’an and Prophetic traditions.